2022
DOI: 10.1038/s41598-022-22044-z
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of chitosan administration on titanium dioxide nanoparticles induced testicular dysfunction

Abstract: The potential reproductive toxic effects of oral TiO2 NPs in adult male rats as well as the possible alleviation of chitosan administration was investigated. Animals were allocated to four groups; the first group received deionized water and was assigned as a control group. In the second group, rats received chitosan at a dose of 5 mg/kg BW/day. The third group was designed for administration of TiO2 NPs at a dose of 150 mg/kg BW/day (1/80 LD50). Rats in the fourth group received both TiO2 NPs and chitosan. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…Aside from lipid metabolism, PPARα can activate cell cycle control genes and stimulate hepatocyte cell proliferation via activation of PCNA. 51,52 Consistent with the expression level of ppar-α, PCNA was also more noticeably overexpressed in male than female carp, especially after exposure to 8:8 PFPiA (Figure S6). The inducement of PCNA might be a compensation for PFPiA-induced apoptosis and necrosis.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Aside from lipid metabolism, PPARα can activate cell cycle control genes and stimulate hepatocyte cell proliferation via activation of PCNA. 51,52 Consistent with the expression level of ppar-α, PCNA was also more noticeably overexpressed in male than female carp, especially after exposure to 8:8 PFPiA (Figure S6). The inducement of PCNA might be a compensation for PFPiA-induced apoptosis and necrosis.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
“…Another possible explanation is based on the fact that the PPAR pathway was activated by binding with FAs, and presumably the uptake of FAs into nuclear for PPAR activation is enhanced in male but depressed in female carp. Aside from lipid metabolism, PPARα can activate cell cycle control genes and stimulate hepatocyte cell proliferation via activation of PCNA. , Consistent with the expression level of ppar-α , PCNA was also more noticeably overexpressed in male than female carp, especially after exposure to 8:8 PFPiA (Figure S6). The inducement of PCNA might be a compensation for PFPiA-induced apoptosis and necrosis.…”
Section: Resultssupporting
confidence: 60%
“…This study was conducted at the Theriogenology department, Faculty of Veterinary Medicine, Mansoura University, Egypt, with an approved animal use protocol (PhD/29) in accordance with the Guiding Principles for the Care and Use of Research Animals. The preparation and characterization of TiO 2 NPs was described in our previous publication [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…This may be caused by dysfunction of steroidogenesis and spermatogenesis after nano-TiO 2 exposure. Several studies have demonstrated a marked decrease in serum T after chronic exposure to nano-TiO 2 (Gao et al, 2013;Jia et al, 2014;Orazizadeh et al, 2014;Hong et al, 2015b;Khorsandi et al, 2017;Morgan et al, 2017;Shahin and Mohamed, 2017;Li et al, 2018;Hussein et al, 2019;Lauvas et al, 2019;Ogunsuyi et al, 2020;Danafar et al, 2021;Liu et al, 2021;Halawa et al, 2022). Li.…”
Section: Effect Of Nano-tio 2 On the Male Reproductive Systemmentioning
confidence: 99%